Erdheim–Chester disease. Literature review and clinical case - A. S. Krylov; M. B. Dolgushin; A. D. Ryzhkov; A. A. Odzharova; Ya. A. Shchipakhina; E. A. Sushentsov; O. P. Bliznyukov; S. M. Kaspshik; A. A. Martinovich; A. M. Stroganova; S. L. Dranko; P. A. Zeynalova; et al. (Онкогематология)
Erdheim–Chester disease (ECD) is a rare and frequently neglected disease, usually with a poor prognosis. The first two cases of ECD were reported by Austrian pathologist: Jakob Erdheim and his apprentice student William Chester in 1930. The etiology and disease incidence are unknown. One of the main components of this disorder is a chronic uncontrollable inflammation. Clinical manifestations of the disease can be very different. ECD affects predominantly adults, usually male population. There is no effective treatment developed yet. In 2016 ECD was classified as histiocytic neoplasm by the World Health Organization and was categorized as “tumors of histiocytes and dendritic cells”. More than half of patients testing positive for the BRAF mutation. There is a Erdheim–Chester Disease Global Alliance (ECDGA), which try to unite and provide with information about diagnostics and treatment of this rare disease both patients and doctors. Today, there are 571 registered patients and only one from Russia. The final diagnosis is made on the basis of histological finding such as infiltration with foamy histiocytes, signs of inflammation and Touton giant cells. Immunohistological analysis is usually CD68 and XIIIa positive. There are radiological finding indicating a possible association with the disease. There is this specific, almost pathognomonic scintigraphic picture of the skeleton, “coated” aorta, “hairy kidney” patterns on computer tomography. We demonstrate a clinical case of a patient with a newly diagnosed ECD with bone and connective tissue involvement, with manifestation of this disease more than 10 years ago. It took four months to make the final diagnosis. There were three biopsies and a wide range of other diagnostic procedures.